Application of supported ionic liquid phase catalyst systems in the hydroformylation of olefin-containing mixtures to aldehyde mixtures with high portion of nonbranched aldehydes. - Franke, Robert; Brausch, Nicole; Fridag, Dirk; Christiansen, Andrea; Becker, Marc; Wasserscheid, Peter; Haumann, Marco; Jakuttis, Michael; Werner, Sebastian; Schönweiz, Andreas (2012)
The subject of the present invention is a catalyst with increased durability based on compn. of (a) an inert, porous substrate, (b) an ionic liq., (c) Rh, (d) a phosphorus-contg. org. ligand, (e) at least an org. amine. A further the subject of the present invention is a procedure for the hydroformylation of olefin-contg. hydrocarbon mixts. to aldehyde mixts. whereby: (a) the water content of the olefin-contg. hydrocarbon mixt. is adjusted to ≤20 ppm, (b) the content of multifunctional unsatd. compds. in the olefin-contg. hydrocarbon mixt. is adjusted continually to ≤3000 ppm, (c) the mol. ratio of org. amines to phosphorus-contg. ligands is ≥4:1; and (d) the mol. ratio of phosphorus-contg. org. ligand to Rh is ≥10:1. A typical catalyst consists of silica support, rhodium acetylacetonate dicarbonyl, bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, 6,6'-[[3,3'-di-tert-butyl-5,5'-dimethoxy[1,1'-biphenyl]-2,2'-diyl]bis(oxy)]bis[dibenzo[d,f][1,3,2]dioxaphosphepin] and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and a typical reaction feed contains 1-butene, isobutene, cis-2-butene, trans-2-butene, n-butane, and isobutane, with the product being n-pentanal. [on SciFinder(R)]
Keywords: ionic liq rhodium phosphorus ligand amine catalyst supported hydroformylation; tertiary butyldimethoxy biphenyldiylbisoxybis dibenzodioxaphosphepin catalyst hydroformylation butene pentanal manuf; hydroformylation olefin catalyst unbranched aldehyde manuf; butene hydroformylation pentanal manuf catalyst; silica support hydroformylation catalyst butene pentanal manuf; rhodium acetylacetonatedicarbonyl catalyst hydroformylation butene pentanal manuf; ethylmethylimidazolium fluoromethanesulfonylimide catalyst hydroformylation butene pentanal manuf

A Scalable Preparation Method for SILP and SCILL Ionic Liquid Thin-Film Materials - Werner, Sebastian; Szesni, Normen; Kaiser, Melanie; Haumann, Marco; Wasserscheid, Peter (Chemical Engineering & Technology, 2012)
Supported ionic liquid phase (SILP) catalysts consist of a homogeneous catalyst that is dissolved in an ionic liquid and dispersed on a porous support material. This immobilization technique yields solid catalysts that can be applied in continuous gas phase processes. Recently, several successful applications have been presented that could possibly lead to a commercialization of this promising class of novel materials. The state-of-the-art preparation method uses an incipient wetness-type impregnation of the support material by a solution of catalyst, ionic liquid, and a helper solvent, followed by subsequent removal of the helper solvent in vacuo. Typically, this removal is carried out in a rotary evaporator, thus being limited in batch size. Similarly, the so-called supported catalysts with ionic liquid layer (SCILL) consist of an ionic liquid layer on top of a traditional heterogeneous catalyst, which can be prepared in a similar way. In this work, a novel preparation method for SILP catalysts is presented that is scalable for larger batches, as required for industrial use. Different types of support materials such as powders, spheres, agglomerates, and extrudates were successfully impregnated by the novel fluidized-bed impregnation method and the distribution of the ionic liquid and catalyst was analyzed by scanning electron microscopy with energy-dispersive X-ray spectroscopy measurements.
Keywords: Energy-dispersive X-ray spectroscopy; Film formation; Fluidized bed; Supported ionic liquid phase; Surface coating

Gas-Phase Hydroformylation of Propene over Silica-Supported PPh3-Modified Rhodium Catalysts - Kim, Taejin; Celik, Fuat E.; Hanna, David G.; Shylesh, S.; Werner, Sebastian; Bell, Alexis T. (Topics in Catalysis, 2011)
Heterogeneous rhodium catalysts supported on SiO_2 were modified with PPh_3 for the gas-phase hydroformylation of propene to produce n- and isobutanal. High selectivity to aldehydes was achieved, with no propane or alcohols formed. Investigation of the effects of reaction temperature, reactant partial pressures, total pressure, and PPh_3/Rh ratio suggested that the supported catalyst behaved similarly to the homogeneous catalyst. In particular, the supported catalyst showed similar activation energies and partial and total pressure dependences of the reaction rates to those observed in homogeneous, liquidphase reactions. The first order dependence of the hydroformylation rate on the partial pressures of propene, CO, and H_2 individually led to a cubic dependence of butanal formation on total pressure for equimolar reactant mixtures. High regioselectivity with a typical n/i ratio of 14 was achieved.
EAM Import::2019-03-13

Homogeneous ruthenium-based water–gas shift catalysts via supported ionic liquid phase (SILP) technology at low temperature and ambient pressure - Werner, Sebastian; Szesni, Normen; Fischer, Richard; Haumann, Marco; Wasserscheid, Peter (Physical Chemistry Chemical Physics, 2009)
Novel ruthenium-based supported ionic liquid phase (SILP) catalysts for the water–gas shift (WGS) reaction are reported which, compared to classical low temperature shift systems, operate at much lower temperatures and even at ambient pressure.

Ionic Liquids in Chemical Engineering - Werner, Sebastian; Haumann, Marco; Wasserscheid, Peter (Annual Review of Chemical and Biomolecular Engineering, 2010)
The development of engineering applications with ionic liquids stretches back to the mid-1990s when the first examples of continuous catalytic processes using ionic liquids and the first studies of ionic liquid–based extractions were published. Ever since, the use of ionic liquids has seen tremendous progress in many fields of chemistry and engineering, and the first commercial applications have been reported. The main driver for ionic liquid engineering applications is to make practical use of their unique property profiles, which are the result of a complex interplay of coulombic, hydrogen bonding and van der Waals interactions. Remarkably, many ionic liquid properties can be tuned in a wide range by structural modifications at their cation and anion. This review highlights specific examples of ionic liquid applications in catalysis and in separation technologies. Additionally, the application of ionic liquids as working fluids in process machines is introduced.

Rhodium-Phosphite SILP Catalysis for the Highly Selective Hydroformylation of Mixed C4 Feedstocks - Jakuttis, Michael; Schönweiz, Andreas; Werner, Sebastian; Franke, Robert; Wiese, Klaus-Diether; Haumann, Marco; Wasserscheid, Peter (Angewandte Chemie International Edition, 2011)
The cat. that got the butene: Highly active and selective diphosphite ligands are applied for rhodium-catalyzed supported ionic liquid phase (SILP) hydroformylation and make it possible to form linear n-pentanal with exceptional selectivity from a mixed butene feedstock by combined isomerization and hydroformylation (see picture, vials 1–4 show typical SILP catalysts employed in this study.). The SILP catalyst is stable for more than 800h on stream.

Screening of Supported Ionic Liquid Phase (SILP) catalysts for the very low temperature water–gas-shift reaction - Werner, Sebastian; Szesni, Normen; Bittermann, Agnes; Schneider, Martin; Härter, Peter; Haumann, Marco; Wasserscheid, Peter (Applied Catalysis A-General, 2010)
Screening of transition metal complexes typically involves elaborative experiments in batch reactors in organic solvents under non-steady-state conditions. In contrast, screening of immobilized catalysts in a fixed-bed continuous gas-phase reactor enables highly efficient and precise investigations on activity and stability under steady-state. In this work we present a technique to immobilize numerous homogeneous transition metal complexes (Ru, Ir, Os, Fe, Cu, Mo, Pd Re, Rh) in the ionic liquid [BMMIM][OTf] on the highly porous support Silica 100 using the Supported Ionic Liquid Phase (SILP) technology. All prepared SILP catalysts were investigated in the water–gas shift reaction (WGSR) in a continuously operated fixed-bed reactor at temperatures between 120 and 160 °C and ambient pressure. Best activities and stabilities were found for ruthenium-based systems.

Supported ionic liquid phase (SILP) catalyzed hydroformylation of 1-butene in a gradient-free loop reactor - Haumann, Marco; Jakuttis, Michael; Werner, Sebastian; Wasserscheid, Peter (Journal of Catalysis, 2009)
The supported ionic liquid phase (SILP) catalysis technology was applied to gas-phase hydroformylation of 1-butene using sulfoxantphos 1 modified rhodium complexes. Kinetic experiments were performed in a fixed bed reactor and compared to a gradient-free gas-phase loop reactor (Berty type). The influence of substrate concentration, temperature and syngas pressure was determined. Data from fixed bed and Berty reactor were found to be in good agreement with respect to activation energy and reaction order. Ex-situ NMR studies of fresh and used SILP catalysts confirmed that the ligand remained intact after prolonged time on stream.

Transition metal carbonyl catalysts with ionic liquids for water gas shift reaction under mild conditions. - Szesni, Normen; Wasserscheid, Peter; Fischer, Richard; Haumann, Marco; Werner, Sebastian; Kaiser, Melanie (2011)
Water gas shift reaction catalysts for reaction under mild conditions use a solid support contg. an active catalyst, an ionic liq., and a co-activator, in which the active catalyst is a metal carbonyl of general formulas [M(CO)x(L)yClz], in which M = Cr, Mo, W, Ru, Fe, Co, Rh, Ir, Mn, Re, Ni, Pd, Pt, Cu, Ag, Au, or Zn; x = 0-6, y = 0-4, z = 1-6, and n = 1, 2, 3, 4, or >4; L is a monodentate or oligodentate donor ligand (e.g., amines, phosphanes, phosphite, arsanes, stibanes, or heterocyclic systems, such as pyridine, bipyridine, phenanthroline, or N-heterocyclic carbene ligands). The ionic liq. is of general structure [A]n+[Y],sup.n- (n = 1 or 2), in which Y is an org. or inorg. anion, and A is an onium cation, such as quaternary ammonium, quaternary phosphonium, sulfonium, guanidinium, imidazolium, pyridinium, pyrazolium, and 1,3,5-triazolium. [on SciFinder(R)]
Keywords: water gas shift catalyst ionic liq; supported ionic liq catalyst water gas shift; metal carbonyl water gas shift catalyst

Ultra-Low-Temperature Water-Gas Shift Catalysis using Supported Ionic Liquid Phase (SILP) Materials - Werner, Sebastian; Szesni, Normen; Kaiser, Melanie; Fischer, Richard; Haumann, Marco; Wasserscheid, Peter (ChemCatChem, 2010)
SILP inside the eye of your mind: A new class of water–gas shift catalyst system that outperforms commercial shift catalysts under ultra-low-temperature real gas conditions (T<160 °C) has been developed. The new catalysts consist of [RuCl2(CO)32] dissolved in a chloride ionic liquid and dispersed on a porous basic support using the SILP approach. Its robustness and recyclability make it highly attractive for industrial hydrogen production.